n-Tuplet Coincidence Point Theorems in Intuitionistic Fuzzy Normed Spaces - Erturk, Muzeyyen; Karakaya, Vatan (HINDAWI LTD, 2014)
For an arbitrary n positive integer, we investigate the existence of n-tuplet coincidence points in intuitionistic fuzzy normed space. Results of the paper are more general than those of the coupled and the tripled fixed point works in intuitionistic fuzzy normed space.
Keywords: CONTRACTIVE TYPE MAPPINGS; FIXED-POINT; NONLINEAR CONTRACTIONS; METRIC-SPACES; Mathematics